RANCANG BANGUN SISTEM PEMANEN ENERGI ANGIN EXHAUST FAN DENGAN TURBIN ANGIN ARCHIMEDES SUMBU HORIZONTAL - Agus Artha Putra, I Made; Indra Partha, Cokorde Gede; Sukerayasa, I Wayan (Jurnal SPEKTRUM; Vol 8 No 2 (2021): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2021.v08.i02.p24, 2021)
Wind ienergy iis iwidely iused ito ireplace ifossil ifuels iwith ivarious itechnologies, ibut iutilization iby iusing iArchimedes iwind iturbines iis istill irarely ifound. iIn ithis ipaper, iresearch iis iconducted ion ithe iimplementation iof ithe iArchimedes iwind iturbine ion ithe iexhaust ifan ito ibe iable ito iutilize ithe iexhaust ienergy iproduced. iThe itest iresults ishow ithat ithe imaximum ipower ican ibe iproduced ireaches i1.91 iW iat ia idistance iof i10 icm, ibut ithe ipower iproduced iis ionly i0.37 iW. iThe ioptimal idistance ito iplace ithe iturbine ito iharvest ienergy iis iat ia idistance iof i30 icm ibecause iat ithat idistance ithe iArchimedes iwind iturbine iis iable ito iharvest ienergy iof i1.54 iW.